The Influence of the Problem Based Learning Model Assisted by Booklet Media on the Understanding Conceptual Ability of Class V Elementary School Students on Water Cycle Material - Murdani, Eka; Sumarli, Sumarli; Ramadhani, Aldi (Universitas Nusantara PGRI Kediri, 2024)
This research aims to determine the effect of the problem based learning model assisted by booklet media on the understanding conceptual ability of fifth grade elementary school students in the water cycle material at SDN 03 Dungun Laut, Jawai District for the 2023/2024 academic year. The type of research used was quantitative research using a quasi experimental design method with a post-test only control group design. The population of this study was all class V students at SDN 03 Dungun Laut, totaling 40 students. The sample for this research was class V with a total of 40 students consisting of class VA with 18 students as the experimental class and class VB with 22 students as the control class. The collection techniques used in this research were test and non-test techniques. The tests used were post-test questions, while non-tests used student response questionnaires, and observation sheets on the implementation of learning activities. The data analysis techniques in this research were the two independent sample t-test, effect size test, and descriptive percentage analysis. The results of the research showed that: (1) There was a difference in students' conceptual understanding between classes that use the problem based learning model assisted by booklet media and classes that are given a direct learning model on water cycle material in class V SDN 03 Dungun Laut with tcount = 2.462 > ttable = 2.024; (2) The influence of the problem based learning model assisted by booklet media on students' science understanding conceptual ability was 0.4 with medium criteria; (3) The implementation of the problem based learning model assisted by booklet media in science learning for class V elementary school was classified as very good with a percentage of 90%; (4) Students response were positive to the problem based learning model assisted by booklet media in science lessons for class V elementary school was 81% with very good criteria. So it could be concluded that the problem based learning model assisted by booklet media had an influence on students' understanding conceptual ability of Natural Science (IPA) in class V water cycle material at SDN 03 Dungun Laut.